MENINGKATKAN KETERAMPILAN BERBAHASA DALAM MENGOLAH KATA BAGI SISWA TUNARUNGU MELALUI METODE STRUKTURAL ANALITIK SINTETIK (Classroom Action Research di SLB YPAC Sumbar) - Rendy Amora J (Universitas Negeri Padang, 2016)
The type of research used was classroom action research with the use of three cycles. Which aims to prove wether the structural analytic synthetic of method language skill increased in the processing words for student deaf. Subject in the research is the teacher and student grade VII. B. Data analysis of the result obtained from the action that are given from one to three cycles. Cycle there is a rise a persen tage of mastery against the aspects set by researchers in processing the wordd become sentence. This proves that method SAS can enhace language proficiency in word processing into sentences for student deaf. Kata Kuci : tunarungu ; keterampilan berbahasa; Mengolah kata ; metode struktural analitik sintetik (SAS)